Nanocompósitos de cerâmicas bioativas para aplicações biomédicas: síntese, caracterização e propriedades - Alves, Erisandra Rodrigues (2011)
Calcium phosphate nanocomposites can be very useful in traumatologic treatments, for the healing of traumatized bone structure, for bone regeneration and bone reconstruction. This work aimed at the production of nanocomposites where a bioceramic matrix is reinforced with nanocrystalline silica (SiO2) particles. The matrix was produced from bioceramic nanopowders (beta tricalcium phosphate, β-TCP) obtained by precipitation in aqueous solution. The nanocomposites were produced in the laboratory by adding nanometric silica particles to the nanometric β-TCP in proportions 15%, 35% e 50% by weight. The material was characterized by x-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX) and diametral compression testing of pressed disk samples. XRD results presented the characteristic peaks of β-TCP, which became less intense as the amount of silica particles increased. FTIR spectra allowed for the identification of groups present in the nanocomposites. SEM micrographs gave an idea of the microstructural of morphological aspects of the material, and showed that the surfaces consisted of a network of interconnected equiaxed particles. It was not possible to observe the dispersion of the silica particles. Diametral compression test results showed that the amount of silica influences the mechanical strength of the nanocomposite.